The Influence of Motivation and Job Satisfaction on Employee Performance at the Plantation and Livestock Service Office of Tolitoli Regency - Ilham Ilham; Aqfir Aqfir; Samsuddin Beddu Messa (Indonesia Auditing Research Journal, 2025)
This study aims to determine the Influence of Motivation and Job Satisfaction on Employee Performance at the Plantation and Livestock Office of Tolitoli Regency. This study uses a quantitative method. The sampling technique used is total sampling. The number of samples in the study was 67 respondents. Data sources are primary data and secondary data. Data collection techniques use questionnaires and documentation. Data analysis techniques use multiple linear regression which is analyzed using the help of SPSS Statistics version 26 data processing tools. Based on the results of the study, it can be concluded that motivation partially influences the performance of employees of the Tolitoli Regency Plantation and Livestock Service. Job satisfaction partially influences the performance of employees of the Tolitoli Regency Plantation and Livestock Service. And motivation and job satisfaction simultaneously influence the performance of employees of the Tolitoli Regency Plantation and Livestock Service